Penerapan Metode Material Requirement Planning (MRP) dalam Pengendalian dan Perencanaan Persediaan Bahan Baku Semen Instan Variasi X pada PT XYZ - Putri Wahyudiana, Qoulina Sakilah; Nurjanah SP.,MT, Noneng; Thorfiani, Dera; Andriyanto,ST.,MT, Achmad (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2023)
XYZ Company is the largest manufacturing company in Indonesia that produces various materials such as instant cement, lightweight bricks (AAC), wall panels, and floor panels. However, the company faces challenges in the supply of raw materials, which hinder the production process and lead to product shortages. The most frequent shortages occur in the 210 instant cement product, with a shortage rate of 99.3% over a six-month period from October 2022 to March 2023. This study employs the Material Requirement Planning (MRP) method to address this issue. The objective is to plan the scheduling of raw material orders and project future requirements. Data on demand, inventory, raw material structures, and supporting data are used in the calculations. As a result, the scheduling of raw material orders for the 210 instant cement product is conducted for three consecutive months, namely April, May, and June 2023. Each month, raw materials such as silica sand, lime, cement, and additives are meticulously planned with several orders based on the lead time of each material.